Deprea zamorae (Physalideae, Solanoideae, Solanaceae): a new species from southern Ecuador - Barboza, Gloria E.; González, Segundo Leiva; García, Carolina Carrizo; Orozco, Clara Inés (Phytotaxa, 2013)
Deprea zamorae Barboza & S. Leiva (Solanaceae), a new species from southern Ecuador (Loja and Zamora–Chinchipe), is described and illustrated. It is most similar to D. cyanocarpa, but differs by the presence of minute teeth on the calyx, the ratio of the corolla tube length to the lobe length, the orientation of the fruiting pedicels, and the color and shape of the fruiting calyx. Its distribution does not overlap with that of any other Deprea species. A key for all Deprea species is provided.